(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Urbanisation is the process by which a greater percentage of a nation’s population moves into urban areas, as opposed to urban expansion, which is characterised by population growth. Urbanisation is the process of turning rural areas into urban areas, and it is stated as a ratio or a percentage of the overall population. One of the most prevalent aspects of economic development is urbanisation. Urbanisation depends on the movement of the surplus population from rural to urban areas as well as the expansion of some industrial urban hubs as the economy expands progressively. Modernization and industrialization are intimately related to urbanisation. In this article, critical review on urban growth and development has been discussed.